Food safety policy in 9 African countries - Grace, Delia; Kang'ethe, Erastus K.; Bonfoh, Bassirou; Roesel, Kristina; Makita, K. (International Livestock Research Institute, 2014)
Introduction Millions of smallholder farmers, many of them women, supply the rapidly growing markets for livestock and fish products in Africa and Asia. In sub Saharan Africa, more than 80% of animal products are sold through informal markets, which lack structured sanitary inspection and are often of ambiguous legal position. Historically food policy has either ignored or been hostile to the informal sector; more recently understanding is growing that the informal food sector can have an important role in supporting livelihoods and improving accessibility to affordable, nutritious foods.